Analisis Persepsi Guru, Siswa dan Orang Tua terhadap Pelaksanaan Pembelajaran PJOK secara Daring di SDN 2 Wulung - Prihantono, Yoga Aji; Setyawati, Heny (Universitas Negeri Semarang, 2023)
The purpose of this study was to describe teacher perceptions, student perceptions, parents' perceptions and the obstacles faced in implementing PJOK online learning. This study uses a descriptive qualitative approach. Data collection techniques using interviews, observation and documentation. The validity of the data is through source triangulation and method triangulation, while data analysis techniques include data reduction, data presentation, and drawing conclusions. The results showed that the implementation of PJOK online learning was carried out through material and practical delivery activities. The teacher's perception is that online learning is not as effective as face-to-face learning. Perceptions of students, students are not happy with online learning because they cannot meet the teacher and their friends. Parents' perception is that the implementation of online learning is less effective, because PJOK lessons have a lot of practice. The obstacles faced by the internet network are less stable and infrastructure facilities that are not yet adequate. In conclusion, the perception of teachers, students and parents towards PJOK online learning is less effective. Suggestions, it is necessary to increase collaboration between teachers, students and parents for the continuity of online PJOK learning in order to achieve the learning objectives that have been set.